Morpho-physiological trait variation of pre-harvest sprouting tolerance to simulated rain in mungbean (Vigna radiata) - RAO, P S; MADHULETY, T Y; ANKAIAH, R; VOLETI, S R (The Indian Journal of Agricultural Sciences, 2023)
Preharvest sprouting (PHS) is one of the most important factors for lower productivity in mungbean [Vigna radiata (L.) R. Wilczek]. The morpho-physiological characters, ultra-structural variations in pods and seeds, changes and regulatory water absorption pathway of 30 mungbean genotypes in relation to pre-harvest sprouting behaviour was studied during kharif 2017–19 at Seed Research Technology Center, Indian Institute of Rice Research, Rajendranagar, Hyderabad, Telangana. Mungbean genotypes subjected to PHS imposed by simulated rainfall were evaluated. Rainfall simulator generates a rainfall spectrum that was similar to natural rainfall. Genotypes LGG 450 and K 851 with low score (%), while ML 267 and MGG 295 with high score (%) were screened as tolerant and susceptible to PHS. Accordingly, higher seed yield was recorded in LGG 450 (4.94 g/plant) followed by K 851 (4.20 g/plant) while lower seed yield was recorded in ML 267 (0.26 g/plant) followed by MGG 295 (0.79 g/plant). The findings were further corroborated with SEM studies by presence of sparse, wiry, short, twist or shriveled trichomes; thick cuticular pod wall, wide locular gap between seed coat (seed) and pod wall helping for the slow diffusion of moisture from endosperm to embryo. Further, the presence of lea-protein-insulated starch grains of endosperm merits lipophilic nature which might hindered dissipation of water to embryo via endosperm. The SEM studies have established ultrastructural features that determine the resistance to pre-harvest sprouting of mungbean and development of future resistant lines identification.